1999
DOI: 10.1557/jmr.1999.0064
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria and crystal chemistry in the Y2O3–Al2O3–SiO2 system

Abstract: In order to clarify inconsistencies in the literature and to verify assumed ternary solubilities, the phase equilibria in the Y2O3–Al2O3 –SiO2 system at 1600, 1400, and 1300 °C were experimentally determined using x-ray diffraction (XRD), scanning electron microscope with attached energy-dispersive detector system (SEM-EDX), and electron probe microanalyzer (EPMA). Six quasibinary phases were observed: Y4Al2O9 (YAM), YAlO3 (YAP), Y3Al5O12 (YAG), Y2SiO5, Y2Si2O7 (C and D modifications), and ˜3Al2O3· 2SiO2 (mull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 26 publications
11
79
0
1
Order By: Relevance
“…It is well known that a small fraction of liquid phase decreases the mullitization temperature. The volume of Al,0 3 and SiO, involved in mullitization is much higher than the glass volume at the eutectic temperature. Therefore, the mullite transformation temperature is highly sensitive to the appearance of the glass phase in the system and must be a good expression of the eutectic temperature.…”
Section: (1) Firing Below 1500°cmentioning
confidence: 88%
See 3 more Smart Citations
“…It is well known that a small fraction of liquid phase decreases the mullitization temperature. The volume of Al,0 3 and SiO, involved in mullitization is much higher than the glass volume at the eutectic temperature. Therefore, the mullite transformation temperature is highly sensitive to the appearance of the glass phase in the system and must be a good expression of the eutectic temperature.…”
Section: (1) Firing Below 1500°cmentioning
confidence: 88%
“…The phase equilibria and crystal chemistry of this system were recently studied by Kolitsch et al , 3 who reported the ternary eutectic temperature to be 13710 ± 5°C. Six quasi-binary phases were found: three yttrium aluminates, two yttrium silicates, and mullite.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…En el caso de la mullita, a partir de una exhaustiva revisión bibliográfica [1][2][3][4][5][6][7] y algunas pruebas preliminares, el aditivo elegido en este estudio fue óxido de itrio (Y 2 O 3 ). Con este aditivo la mullita sinteriza por fase líquida, como cabe esperar a partir del diagrama de fases del sistema ternario SiO 2 -Al 2 O 3 -Y 2 O 3 , que ha sido publicado en un trabajo reciente 9 . En un sistema de micromorfología análoga a la mullita, como es el Si 3 N 4 , está bien documentado que la adición de Y 2 O 3 mejora la sinterización mediante la formación de líqui-dos [10][11][12] .…”
Section: -Introducciónunclassified